A novel monocanalicular silicone intubation technique for canalicular laceration repair. Issue 8 (August 2021) - Zhang, Wei; Zhang, Dingguo; Han, Pengfei; Liang, Xing; Zhang, Weiliang; Feng, Feng; Shao, Ying
Summary: Objectives: This study aimed to evaluate the clinical efficacy and reliability of a novel monocanalicular silicone intubation (nMCI) technique for canalicular laceration repair in a series of patients treated over a 3-year period. Methods: The case records of 86 patients (86 eyes) who had undergone nMCI-based surgical repair of canalicular lacerations were retrospectively reviewed. The silicone tube removal was planned for 3 months postoperatively. A minimal follow-up of 6 months was adopted for the final analysis. The primary outcome measures included anatomical patency on irrigation and relief from epiphora, which were assessed subjectively and objectively through a fluorescein dye disappearance test. Results: A total of 86 patients (72 males and 14 females; mean age = 34 years) were included. The upper canaliculus was damaged in 13 cases, while the lower canaliculus was damaged in 73 cases. Successful stenting was achieved in all cases. The postoperative eyelid position was satisfactory in the majority of the patients. The mean period of stenting was 3 months, while the mean postoperative follow-up period was 6 months. There were no cases of premature stent extrusion. The functional drainage following stent removal was normal in 95% of the patients, while the syringing revealed full patency with no narrowing or reflux. Conclusion: The present results suggest that the nMCI technique presents an effective and atraumatic surgical approach for adult patients with canalicular lacerations. The main advantages of the technique are the simple insertion and the easy removal of the tube, which results in high anatomical and functional success rates and offers an effective alternative in the treatment of monocanalicular lacerations.